1979
DOI: 10.1111/j.1439-0329.1979.tb00679.x
|View full text |Cite
|
Sign up to set email alerts
|

Beech Bark Disease: A Comparison of the Disease in North America, Great Britain, France, and Germany

Abstract: Sensibilite des jeunes rameaux de Peuplier au M. brunnea 199 Pustules tend to be crowded at the ba.ses of ttie shoots and they seem to be independent of late infection on foliage. Ttiis suggests that shoots have a characteristic pattern in the development of .susceptibility during development. ZusammenfassungDie Anfdlligkcit junger Pappeltriebe gegen Marssonina brunnea (Ell. et Ev.) P. magn. Registriert wurde die Anzahl von Marssonina brunnea-Pusteln an Trieben versehiedener Pappelklone. Eine diesbeziigli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
5

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 8 publications
0
14
0
5
Order By: Relevance
“…Based on an extensive comparative study of BBD in North America, Great Britain, France and Germany, "there is relatively little consistent or conclusive evidence to link environmental factors to population trends of C. fagi or to the cause of beech bark disease" [88]. A recent study in Germany focused on European beech management has shown no correlation between management practices and the infestation rate of the beech scale [41].…”
Section: Possible Mechanisms Of Resistance Environmental Factorsmentioning
confidence: 99%
“…Based on an extensive comparative study of BBD in North America, Great Britain, France and Germany, "there is relatively little consistent or conclusive evidence to link environmental factors to population trends of C. fagi or to the cause of beech bark disease" [88]. A recent study in Germany focused on European beech management has shown no correlation between management practices and the infestation rate of the beech scale [41].…”
Section: Possible Mechanisms Of Resistance Environmental Factorsmentioning
confidence: 99%
“…Beech bark disease was introduced from Europe through the port of Halifax in the late 19th century and has swept through all of the region except the northern third of New Brunswick, where the climate is apparently too cold for survival of the scale insect-fungus complex that causes the disease. In areas of New England, up to 85% of the trees died in the first wave of the disease (Houston et al 1979). Comparable statistics are not available for the Acadian Forest Region but it is likely that the mortality rate was similar.…”
Section: Major Forest Types and Human Impactsmentioning
confidence: 99%
“…Three human-introduced diseases have had, or probably soon will have, significant impacts on tree species in the tolerant hardwood forest types: beech bark disease (Houston et al 1979) and Dutch elm disease (Magasi et al 1981), which have spread through much of the Acadian forest, and butternut canker (Harrison et al 1998), which is just entering the region. Beech was once a major component of tolerant hardwood and mixedwood forest types.…”
Section: Major Forest Types and Human Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…We know that feeding by C. fagisuga results in reduced growth and some bark necrosis. While some of us feel that C. fagisuga can cause extensive bark necrosis (Braun, 1977), most of us feel that under normal growth conditions, death of bark attributable to the insect alone is relatively limited (Boodle and Dallimore 1911 ;Ehrlich, 1934 ;Hartig, 1878 ;Parker, 1974 ;Shigo, 1964 ;Thomsen et al, 1949 (Braun, 1977), the majority of us believe that they are primarily responsible for bark necrosis, and ultimately for tree mortality (Houston et al, 1979a).…”
mentioning
confidence: 99%